Priming fingerprint induced by Bacillus amyloliquefaciens QV15, a common pattern in Arabidopsis thaliana and in field-grown blackberry - Enrique Gutierrez Albanchez; Ana García-Villaraco; José A. Lucas; Francisco J. Gutierrez; Beatriz Ramos-Solano (Journal of Plant Interactions, 2018)
The aim of this study is focused on determining the Bacillus amyloliquefaciens QV15 priming fingerprint in two different plant species, Arabidopsis and blackberry as a crop of agronomic interest, associated with protection upon pathogen challenge. To achieve this goal, Arabidopsis thaliana plants were challenged with Pseudomonas syringae DC3000 under controlled conditions, and field-grown blackberries were challenged by a powdery Mildew outbreak, finding plant protection in plants treated with QV15, in both conditions. Changes in ROS scavenging enzymes’ activity, defense-related enzymes’ activity and gene expression were evaluated in both plant species, before and after pathogen challenge, revealing the ability of this strain to prime both. As a result of this analysis, the priming fingerprint induced by QV15 was defined by a decrease in ROS scavenging enzymes’ activity in pre- and post-challenged plants, an increase in glucanase and chitinase activity after pathogen challenge, significantly increasing the expression of PR1, indicating a salicylic acid (SA)-mediated pathway activation. These results suggest an excellent potential of B. amyloliquefaciens QV15 to protect different plant species against different pathogens in field conditions.